A Discourse Stylistics Analysis on the Regularities in Alice Walker’s The Color Purple - Zamruddin, Mardliya Pratiwi; Arafah, Burhanuddin (KnE Social Sciences, 2019)
The purpose of this study was to describe the regularities of the American Postmodern Novelist: Alice Walker with a focus on a character’s and/or narrator’s mind style in a stylistic and narratological approach. This study aimed to attain the regularities from the American novelist’s literary work and how the regularities/irregularities occur in the novel to frame the style of the novelist in producing her literary work. This study was a descriptive qualitative by taken into account of stylistics categories and mind style which were applied to the Alice Walker’s The Color Purple. The data of this study were taken from Alice Walker’s novel entitled The Color Purple. The result of the study showed the occurrences and the forms of regularities in the novel The Color Purple by Alice Walker which represented the style of the novelist in creating her literary work. The bold character of African-American Vernacular English that were found in Alice Walker’s The Color Purple showed that the novelist poured their mind style in their literary works by showing their stylistic options in producing the novel. By showing their writing style the novelists were contributed to the development of national language in America. Keywords: discourse stylistics, mind style, postmodern, American novelist, AfricanAmerican